A metal-organic framework modulated to site-isolate Cl˙ pendants via radical inter-conversion for degrading hard-to-ionize aqueous organic wastes - Kim, Minsung; MD AL MAMUNUR RASHID; Choe, Yun Jeong; Kim, Sang Hoon; Lee, Jung-Hyun; Jeong, Keunhong; Kim, Jongsik (Royal Society of Chemistry, 2023)
Compared with conventional OH, Cl is longer-lived, more selective to destabilizing refractory electron (e(-))-donating aqueous aromatics via radicalization, and renewable via e(-) transfer from aromatics to enable Cl <-> Cl- inter-conversion. To demonstrate the merits of Cl, a Cl pendant (Cl-SUP)-functionalized Zr-based metal-organic framework (UiO-66-Cl) was synthesized/modulated to impart mesoporosity for facilitating the diffusion of bulky aromatics into the porous architecture. UiO-66-Cl could site-isolate Cl- anions (Cl-SUP(-)) near Lewis acidic Zr4+ cations (LA) and Bronsted acidic -OH (BA), on which OH was produced via homolytic H2O2 dissection, desorbed, and bound to Cl-SUP(-) to yield Cl(SUP)via exothermic radical inter-conversion of OH -> Cl-SUP (referred to as the overall OH -> Cl-SUP route). UiO-66-Cl provided greater LA/BA strengths than UiO-66 un-functionalized with Cl-SUP/Cl-SUP(-), thus requiring a lower energy for OH desorption, which was identified as the rate-determining step of homolytic H2O2 dissection on UiO-66 or the overall OH -> Cl-SUP route on UiO-66-Cl. Consequently, Cl-SUP productivity on UiO-66-Cl was higher than OH productivity on UiO-66 (activity up arrow). Moreover, UiO-66-Cl exploited Cl-SUP as the major decomposer of e(-)-donating aromatics (selectivity up arrow) via the e(-) transfer pathway (recyclability up arrow), as proved by DFT calculations, EPR spectroscopy, and filtration/scavenging/isotope control runs. Furthermore, UiO-66-Cl was more resistant to structural deformation upon exposure to extreme reaction environments than UiO-66 (stability up arrow), as verified by DFT calculations/XRD analysis. Hence, UiO-66-Cl (Cl-SUP) outperformed UiO-66 (OH), SO42--functionalized iron oxide (SO4SUP-), or NO3--modified Mn oxide (NO3SUP) in degrading e(-)-donating, ionization-resistant aqueous aromatics (phenol, aniline, acetaminophen, sulfanilamide, and sulfamethoxazole) in terms of activity, selectivity, stability, and/or reusability.